The location of surgical care for rural patients with rectal cancer: patterns of treatment and patient perspectives - Nostedt, Michelle C. (Can J Surg, 2014)
BACKGROUND: Where cancer patients receive surgical care has implications on policy and planning and on patients’ satisfaction and outcomes. We conducted a population-based analysis of where rectal cancer patients undergo surgery and a qualitative analysis of rectal cancer patients’ perspectives on location of surgical care. METHODS: We reviewed Manitoba Cancer Registry data on patients with colorectal cancer (CRC) diagnosed between 2004 and 2006. We interviewed rural patients with rectal cancer regarding their preferences and the factors they considered when deciding on treatment location. Interview data were analyzed using a grounded theory approach. RESULTS: From 2004 to 2006, 2086 patients received diagnoses of CRC in Manitoba (colon: 1578, rectal: 508). Among rural patients (n = 907), those with rectal cancer were more likely to undergo surgery at an urban centre than those with colon cancer (46.5% v. 28.8%, p < 0.001). Twenty rural patients with rectal cancer participated in interviews. We identified 3 major themes from the interview data: the decision-maker, treatment factors and personal factors. Participants described varying input into referral decisions, and often they did not perceive a choice regarding treatment location. Treatment factors, including surgeon factors and hospital factors, were important when considering treatment location. Personal factors, including travel, support, accommodation, finances and employment, also affected participants’ treatment experiences. CONCLUSION: A substantial proportion of rural patients with rectal cancer undergo surgery at urban centres. The reasons are complex and only partly related to patient choice. Further studies are required to better understand cancer system access in geographically dispersed populations and to support cancer patients through the decision-making and treatment processes.